Las autoridades de los pueblos y la organización nacional. Cuestiones de soberanía entre la Confederación Argentina y Buenos Aires tras la batalla de Cepeda (1859) - Mariana Canedo (Nuevo mundo - Mundos Nuevos, 2023)
The complex processes of nineteenth-century nation-state building included ways of settling prerogatives between national, provincial and municipal governments. This article focuses on the tensions generated by the government of the rural towns between the Estado de Buenos Aires and the Confederación Argentina at a time of debates and confrontations over the organisation of the national state in the mid-nineteenth century. The aim is to analyse the different changes of authorities generated in the rural towns as a resonance of the confrontations over the constitution of the nation state and as an expression of tensions over the self-government of local communities. A significant number of cases are reconstructed and articulated in order to consider the interests and actions adopted by different actors in the different changes of authorities around the battle of Cepeda. We consider the disputes over the appointment of authorities in the towns as issues of representation and self-government typical of the nineteenth century that were articulated with policies of domination deployed at a time of armed clashes and tensions in the relations between the capital city and the rural towns.